JSE 26:3 Fall 2012 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2012)
I’ve been looking back on what’s happened with the JSE since we parted ways with our former publisher, Allen Press, and switched to a more cost-effective and flexible online publishing system that allowed us to offer both print and electronic versions of the Journal. We were quite sure, when this happened, that the transition would reduce our production costs, and we figured that the savings could partially be passed along to readers by allowing us to increase the size of our journal issues—provided (of course) that we had enough acceptable submissions to sustain the increase. I predicted at the time that we’d probably be able to add about 100 pages annually to the JSE. And I’m pleased to report that the prediction has so far panned out, by a comfortable margin. So I submit the following for your consideration.